Effect of nutrition education and psychosocial factors on child feeding practices: findings of a field experiment with biofortified foods and different women categories - Mutiso, J.M.; Okello, J.J.; Lagerkvist, Carl Johan; Muoki, Penina Ngusye; Kosura, W.O.; Heck, S. (Informa UK Limited, 2018)
Despite the efforts to promote good practices in infant and young child feeding (IYCF), the adoption of such practices has been low. Using data from a sample of 665 women, and the theory of planned behavior, we examine the effect of different types of nutrition education and psychosocial factors on the use of recommended IYCF practices. Regression results show that nutrition education and psychosocial factors have strong positive effect on the extent to which IYCF practices are used, with the latter having conflicting individual but overall positive effect. Moreover, coefficients of latter were mostly less than those of the former indicating that pschosocial factors were less important in explaining variability in usage of IYCF than the nutrition education variables. It further finds that different sets of nutrition education and psychosocial factors affect different categories of women, with interactive nutrition education approaches having a greater effect. The findings also suggest need for targeting of beneficiaries with multiple nutrition education approaches.